COVID-19 SEBAGAI FENOMENA RELASI EKSAMINATIF (‘ALAQAH AL-IBTILA) DALAM PENDIDIKAN ISLAM: KAJIAN FILOSOFIS PEMIKIRAN MAJID IRSAN AL-KILANI - Debi Fajrin Habibi; Kambali Kambali (al-Afkar, Journal For Islamic Studies, 2020)
This article discusses the Covid-19 phenomenon in the perspective of Majid Irsan Al-Kilani's perspective of Islamic education. In his book titled Falsafah Al-Tarbiyah Al-Islamiyyah : Dirasah Muqaranah baina Falsafah Al-Tarbiyah Al-Islamiyyah wa Al-Falsafat Al-Tarbawiyyah Al-Mu'ashirah, Al-Kilani discusses one vision of Islamic education, is intertwined harmonious relations between humans and life is called 'Alaqah Al-Ibtila or examinative relations. Covid-19 is one of the tests that is currently endemic in almost the entire world, and has an impact not only on the health sector, but also on the economy and the education process. Humans as perpetrators of the educational process can not be separated from the test. This paper has the concept of double movement, in the sense of a review of the Covid-19 phenomenon as a form of testing for humans, and at the same time assessing the impact of the test on current educational conditions.